Seismic vulnerability assessment to earthquake at urban scale: A case of Mostaganem city in Algeria - Belkacem Chaibedra; Abdelkader Benanane; Zahra Boutaraa (Jàmbá, 2018)
The focus of this study was the seismic vulnerability assessment of buildings constituting Mostaganem city in Algeria. Situated 320 km to the west of Algiers, Mostaganem city encompasses a valuable cultural and architectural built heritage. The city has suffered several moderate earthquakes in recent years; this has led to extensive structural damage to old structures, especially unreinforced historical buildings. This study was divided into two essential steps, the first step being to establish fragility curves based on a non-linear static pushover analysis for each typology and height of buildings. Twenty-seven pushover analyses were performed by means of SAP2000 software (three analyses for each type of building). The second step was to adopt the US HAZUS software and to modify it to suit the typical setting and parameters of the city of Mostaganem. A seismic vulnerability analysis of Mostaganem city was conducted using HAZUS software after inputting the new parameters of the fragility curves established within the first step. The results indicated that the number of poor-quality buildings expected to be totally destroyed under a 5.5 Mw earthquake scenario could reach more than 28 buildings. Three percent of unreinforced masonry (URM) buildings were completely damaged and 10% were extensively damaged. Of the concrete frame buildings, 6% were extensively damaged and 19% were moderately damaged. According to the built year, 6% of both concrete frame and URM buildings built before 1980 are estimated to be collapsing. Buildings constructed between 1980 and 1999 are more resistant; 8% of those structures were extensively damaged and 18% were moderately damaged. Only 10% of buildings constructed after 1999 were moderately damaged. The results also show that the main hospital of the city, built before 1960, will be extensively damaged during an earthquake of 5.5 Mw. The number of human casualties could reach several hundreds – 10.5% of residents of URM buildings are injured or dead. Compared with the URM buildings, concrete frame buildings have lower casualty rates of 1.5% and 0.5% for those built before and after 1980, respectively. It was concluded that Mostaganem city belongs to seismic vulnerable zones in Algeria; in this regard, an action plan is needed for the rehabilitation of old constructions. In addition, the effectiveness of establishing and introducing new and appropriate fragility curves was demonstrated.